3.2 Airway Cell Biology and Immunopathology 2016
DOI: 10.1183/13993003.congress-2016.pa3986
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of actin dynamics by WNT-5A: Implications for human airway smooth muscle contraction

Abstract: A defining feature of asthma is airway hyperresponsiveness (AHR), which underlies the exaggerated bronchoconstriction response of asthmatics. The role of the airway smooth muscle (ASM) in AHR has garnered increasing interest over the years, but how asthmatic ASM differs from healthy ASM is still an active topic of debate. WNT-5A is increasingly expressed in asthmatic ASM and has been linked with Th2-high asthma. Due to its link with calcium and cytoskeletal remodelling, we propose that WNT-5A may modulate ASM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Alternatively, the high endogenous expression of WNT5A in smooth muscle may have obscured potential effects. We found that basal expression levels of WNT5A in airway smooth muscle and elastic arteries were already very high and our previous studies have shown that WNT5A in freshly isolated human ASM is higher than that in cultured human ASM cells 16 . Moreover, whereas our previous studies showed effects of WNT5A knockdown on TGF-β-induced matrix protein and α-SMA expression, recombinant WNT5A by itself did not have such effects 16 .…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Alternatively, the high endogenous expression of WNT5A in smooth muscle may have obscured potential effects. We found that basal expression levels of WNT5A in airway smooth muscle and elastic arteries were already very high and our previous studies have shown that WNT5A in freshly isolated human ASM is higher than that in cultured human ASM cells 16 . Moreover, whereas our previous studies showed effects of WNT5A knockdown on TGF-β-induced matrix protein and α-SMA expression, recombinant WNT5A by itself did not have such effects 16 .…”
Section: Discussionmentioning
confidence: 50%
“…We found that basal expression levels of WNT5A in airway smooth muscle and elastic arteries were already very high and our previous studies have shown that WNT5A in freshly isolated human ASM is higher than that in cultured human ASM cells 16 . Moreover, whereas our previous studies showed effects of WNT5A knockdown on TGF-β-induced matrix protein and α-SMA expression, recombinant WNT5A by itself did not have such effects 16 . Collectively, these previous studies and our current findings may point towards a role of WNT5A as a facilitator, rather than instigator of airway remodelling, and that WNT5A is required but not sufficient to promote the asthmatic pathology.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations